Sequência didática com uso do software Scratch para o ensino da classificação dos triângulos quanto aos seus lados e ângulos - Rigoti, Carlos Eduardo Dominicali (2022)
With the advance in technology and science, traditional teaching methods are no longer so effective in the teaching-learning process. We live in a century of constant transformations, in which the foundations of knowledge must be supported by creative learning and student protagonism. It is necessary to pursue new strategies to approach subjects of mathematical knowledge in a playful and active manner. Therefore, based on this problematic we developed this work, which consisted on the application of a didactic sequence for studying triangle classification, executed with 9th grade students from a state high school of the Umuarama education nucleus, resorting the rotations by stations model and the Software Scratch. The didactic sequence was formulated based on subjects of knowledge from the Geometry thematic unit, of the curricular component of Mathematics and its Technologies, Five work phases were staged with activities and programming routines on Scratch. A test with questions from previous years of the SAEB’s test was applied as a form of assessment of the covered content, which revealed interesting results, around 78% of hits. Another importante result was the progress of the school’s Math grades in the SAEB’s test by 7,32 points, revealing that the didactic sequence and the use of Scratch significantly contribute to student’s learning.